2000
DOI: 10.1530/jrf.0.1200397
|View full text |Cite
|
Sign up to set email alerts
|

Identification of perivitelline N-linked glycans as mediators of sperm-egg interaction in chickens

Abstract: This study demonstrates that carbohydrates play an essential role in sperm-egg interactions in birds. Sperm-egg interaction was measured in vitro as the ability of spermatozoa to hydrolyse a small hole in the inner perivitelline layer, the equivalent of the mammalian zona pellucida. Preincubation with Triticum vulgaris lectin (WGA) and succinyl-WGA (S-WGA) at 10 microgram ml(-1) resulted in complete inhibition of sperm-egg interaction, whereas at the same concentration a range of other lectins (Canavalia ensif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 6 publications
(2 reference statements)
2
15
0
1
Order By: Relevance
“…Although it appears that there is participation by N-linked oligosaccharides, we did not investigate the involvement of o-glycans of ZP1 in the induction of the AR in quail. However, Robertson et al (2000) have demonstrated that the pretreatment of chicken PL with o-glycanase does not reduce the number of holes after incubation with ejaculated spermatozoa in vitro. A determination of the carbohydrate structure of ZP1 required for AR induction in quail must await future analysis, however, our lectin blot analysis indicated the presence of N-acetylglucosamine in the sugar moiety of ZP1 protein, which is recognized with RCA 120 and PHA-E 4 .…”
Section: Acrosome Reaction In Japanese Quailmentioning
confidence: 95%
See 1 more Smart Citation
“…Although it appears that there is participation by N-linked oligosaccharides, we did not investigate the involvement of o-glycans of ZP1 in the induction of the AR in quail. However, Robertson et al (2000) have demonstrated that the pretreatment of chicken PL with o-glycanase does not reduce the number of holes after incubation with ejaculated spermatozoa in vitro. A determination of the carbohydrate structure of ZP1 required for AR induction in quail must await future analysis, however, our lectin blot analysis indicated the presence of N-acetylglucosamine in the sugar moiety of ZP1 protein, which is recognized with RCA 120 and PHA-E 4 .…”
Section: Acrosome Reaction In Japanese Quailmentioning
confidence: 95%
“…A determination of the carbohydrate structure of ZP1 required for AR induction in quail must await future analysis, however, our lectin blot analysis indicated the presence of N-acetylglucosamine in the sugar moiety of ZP1 protein, which is recognized with RCA 120 and PHA-E 4 . It is of interest to note that the sperm hydrolysis of the PL in chicken was inhibited when N-acetylglucosamine was included in the incubation mixture (Robertson et al 2000).…”
Section: Acrosome Reaction In Japanese Quailmentioning
confidence: 99%
“…The sperm glycocalyx is highly complex and heavily sialylated and modification of the glycocalyx results in reduced fertility and failure of the sperm to enter the SSTs [64][65][66][67]. Interestingly, removal of membrane-associated carbohydrates did not affect sperm entry into SSTs if sperm were inseminated directly into the UVJ or when co-incubated with UVJ explants, suggesting the glycocalyx plays a central role in sperm transport and selection through the vagina [64,66,68]. Further barriers to sperm prior participating in the process of fertilization include sperm release from the SST and subsequent transport to the infundibulum, and their interaction with the ovum (reviewed in [69]).…”
Section: Oviductal Sperm Selection Transport and Storagementioning
confidence: 99%
“…It is clear, however, glycoproteins play a large role in the interaction between the sperm and ova, even if not directly involved in targeting of sperm to the GD in vivo [71]. Pre-treatment of either the PL or sperm with N-glycanases resulted in significantly decreased sperm-ovum interaction in vitro [68,71]. Conversely, N-linked oligosaccharides released from the inner PL by N-glycosidase treatment could induce the acrosome reaction in sperm in vitro [72].…”
Section: Sperm: Ovum Interaction and Fertilizationmentioning
confidence: 99%
“…A confiabilidade no teste de adesão a MP externa pode ser questionada, uma vez que os espermatozoides que não sofreram o processo de capacitação, reação do acrossoma e transposição da zona pelúcida podem se aderir à MP externa (ROBERTSON et al, 2000). Já no teste de penetração na MP interna, são avaliados diretamente os orifícios provocados pela ação hidrolítica das enzimas acrossomais, após o processo de capacitação espermática.…”
Section: Concentrações Deunclassified